The theory of punishment in Hegel’s legal thought - Herszenbaun, Miguel Alejandro (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2017)
Hegel’s legal thought has been considered in at least three works published while the author was alive: the Phenomenology of Spirit, the Encyclopedia and the Philosophy of Right. The main problem while considering Hegel’s treatment of Penal Law is based on a lack of attention to its systematic location on Hegel’s work and a lack of articulation between the legal subject and the Hegelian thought. In this paper, I offer an interpretation on the grounds of the Penal Law. This interpretation takes into account the systematic location of the legal subject and main aspects of Hegel’s philosophy.